IMPACT OF INTEREST RATE CHANGES ON CONSUMER BANKING BEHAVIOR (International Journal of Food and Nutritional Sciences, 2023)
This study explores how changes in interest rates shape consumer decisions and financial markets. Interest rates are fundamental drivers of consumer banking behavior, influencing savings, borrowing, investments, and overall economic activity. Higher interest rates incentivize saving by offering higher returns on deposits such as savings accounts and certificates of deposit (CDs). This encourages consumers to prioritize saving over spending, contributing to economic stability and personal financial security. Conversely, lower interest rates diminish the attractiveness of traditional savings options, prompting consumers to seek alternative investments or increase discretionary spending. Changes in interest rates directly impact the cost of borrowing for consumers. When rates rise, borrowing becomes more expensive, leading to reduced demand for mortgages, auto loans, and credit cards. In contrast, lower interest rates stimulate borrowing activity as consumers take advantage of cheaper loans, fostering economic growth through increased consumer spending and investment. Interest rate fluctuations influence investment strategies, guiding asset allocation decisions among consumers. Higher rates may attract investors to fixed-income securities like bonds, while lower rates encourage riskier investments in equities and real estate. These shifts in investment preferences can affect market dynamics and investor confidence. The broader economic implications of interest rate changes include impacts on inflation, employment, and currency values. Central banks adjust rates to manage these indicators, aiming to achieve sustainable economic growth and price stability. Consumer sentiment and spending patterns respond sensitively to these changes, reflecting perceptions of future economic conditions.Understanding the intricate relationship between interest rates and consumer banking behavior is crucial for policymakers and financial institutions. Effective management of interest rate policies can support consumer financial health, economic stability, and sustainable growth. As global economies navigate uncertainties, the impact of interest rate changes remains a critical area of study and adaptation in consumer banking dynamics.